Fieldwork as performance: being ethnographic in film-making. Issue 2 (3rd April 2019) - Koch, Julia
Abstract : This paper examines the use of the visual medium of collaborative ethnographic film-making as a fieldwork method in anthropology. Focusing on practices of filming, I adapt Richard Schechner's ideas of performance processes and relational quadrilogues to move beyond the dichotomy of factual "documentation" versus non-factual "fiction." Instead I think around complicity to reconfigure "ethnographic authority" in film-making as a fieldwork practice. The paper considers the making of the ethnographic film Kabul Kiya? Do You Accept? by Julia Koch, Helen Basu and Andreas Samland, which focuses on Islam, marriage and migration between Africa and India. The paper centres on the multiplicity of the collaborative relationships between those involved in making the film: two of the protagonists, two anthropologists and a full-time cinematographer.